Applying singular perturbation to the stochastic model of the Michaelis-Menten mechanism - Khoo, Chin Foon (2009)
We apply singular perturbation to the chemical master equation of the Michaelis-Menten mecha- nism. Singular perturbation is used to simplify the model and derive a lower dimensional approximation.